Economic impact of hypoglycemia among insulin-treated patients with diabetes. (1st November 2016) - Sussman, Matthew; Sierra, Joseph A; Garg, Satish; Bode, Bruce; Friedman, Mark; Gill, Max; Kaufman, Francine; Vigersky, Robert; Menzin, Joseph
Abstract: Objective: The objective of this study was to assess the cost of hypoglycemic events among insulin-treated patients with diabetes and the potential cost savings to a hypothetical US health plan and employer of reducing hypoglycemic events with a device intervention. Methods: A cost-calculator model was developed to estimate the direct costs of hypoglycemic events, accounting for diabetes type, age, and event severity. Model inputs were derived from published incidence rates of hypoglycemic events and direct medical costs. Assumed intervention efficacy was based on published studies of an emerging technology which yielded 72.2% (LGS Trial; ACTRN12610000024044) and 31.8% (ASPIRE Trial; NCT01497938) reductions in severe and non-severe hypoglycemic events, respectively. Model outcomes—including the number of severe (requiring medical assistance) and non-severe events, and direct/indirect medical costs (excluding intervention costs)—were evaluated over a 1-year period for a hypothetical health plan and employer perspectives. Results: In a health plan with 10 million enrollees, patients without the intervention would have experienced 0.09 and 14.60 severe and non-severe hypoglycemic events per patient per year (PPPY), respectively (vs 0.02 severe and 9.96 non-severe events with the intervention). This translated into total direct medical cost savings of 45 million (177 PPPY) for the health plan. For an employer with 100, 000 employees, the intervention would have yielded additional savings of 492 PPPY in indirect costs. Conclusion: Insulin-treated patients experience hypoglycemic events, which are associated with substantial direct and indirect medical costs. The cost savings of reducing hypoglycemic events need to be weighed against the costs of using diabetes device interventions.